Correlated flickering of erythrocytes membrane observed with dual time resolved membrane fluctuation spectroscopy under different d-glucose concentrations - J. Tapia (Nature Portfolio, 2021)
Abstract A correlated human red blood cell membrane fluctuation dependent on d-glucose concentration was found with dual time resolved membrane fluctuation spectroscopy (D-TRMFS). This new technique is a modified version of the dual optical tweezers method that has been adapted to measure the mechanical properties of red blood cells (RBCs) at distant membrane points simultaneously, enabling correlation analysis. Mechanical parameters under different d-glucose concentrations were obtained from direct membrane flickering measurements, complemented with membrane fluidity measurements using Laurdan Generalized Polarization (GP) Microscopy. Our results show an increase in the fluctuation amplitude of the lipid bilayer, and a decline in tension value, bending modulus and fluidity as d-glucose concentration increases. Metabolic mechanisms are proposed as explanations for the results.